Cultural strategies: how do national cultures impact the operations strategy? - Lee Park, Camila Hyeun (2015)
Through the assessment of the fourth round of the High Performance Manufacturing (HPM) project and the introduction of Hofstede’s Cultural Classification, the present work aims to deepen the comprehension of the impact of National Cultures on firms’ Operations Strategy. The ANOVA comparisons of four Operations Strategy elements in countries with different industrialization and development backgrounds (e.g. Germany, China, Brazil and South Korea) suggest that while Integrating Leadership and Implementation of Manufacturing Strategy are affected by the cultural levels of Power Distance, Individualism vs. Collectivism and Uncertainty Avoidance, the other two elements of Operations Strategy, Functional Integration and Formal Manufacturing Strategy, show effects of the degree of Individualism vs. Collectivism and Long-Term Orientation. The results of the study are expected to offer new perspectives on the planning and implementation of strategic and operations management for both practitioners and academics. More specifically, the analysis of cross-cultural influence over operations strategy may contribute to a better understanding of how cooperative behavior may lead firms to generate higher rents through the strengths and weaknesses of their relations, particularly in terms of global supply chains.